Effect of Macular Internal Limiting Membrane Peeling on Single Surgery Success Rates of Vitrectomy for Uncomplicated, Primary Macula-Off Retinal Detachment. (May 2023) - Martens, Rosanna K.; Chen, Chao; Ehmann, David S.; Greve, Mark; Seamone, Mark E.
Purpose: To determine the anatomic and visual outcomes of pars plana vitrectomy for uncomplicated, primary macula-off rhegmatogenous retinal detachment (RRD) with and without internal limiting membrane (ILM) peeling.Methods: This retrospective chart review comprised 129 patients with uncomplicated, primary macula-off RRD presenting between January 1, 2016, and May 31, 2021. Thirty-six patients (27.9%) had ILM peeling and 93 (72.0%) did not. The primary outcome was the rate of recurrent RRD. Secondary outcomes included preoperative and postoperative best-corrected visual acuity (BCVA), epiretinal membrane (ERM) formation, and macular thickness.Results: No significant difference was found in the risk for recurrent RRD between patients who had ILM peeling and those who did not (2.8% [1/36] and 5.4% [5/93], respectively) ( P = 1.00). The final postoperative BCVA was better in eyes that did not have ILM peeling ( P < .001). No ERM occurred in the group with ILM peeling, whereas ERM occurred in 27 patients (29.0%) who did not have ILM peeling. The temporal macular retina was thinner in eyes in which ILM peeling was performed.Conclusions: The risk for recurrent RRD was not statistically lower in eyes having ILM peeling of the macula in uncomplicated, primary macula-off RRD. Despite a reduction in postoperative ERM formation, eyes having macular ILM peeling had worse postoperative VA.